The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/03079457.2021.1873246
|View full text |Cite
|
Sign up to set email alerts
|

The bird’s immune response to avian pathogenic Escherichia coli

Abstract: Avian pathogenic Escherichia coli (APEC) cause colibacillosis in birds, a syndrome of severe respiratory and systemic disease that constitutes a major threat due to early mortality, condemnation of carcasses and reduced productivity. APEC can infect different types of birds in all commercial settings, and birds of all ages although disease tends to be more severe in younger birds likely a consequence of an immature immune system. APEC can act as both primary and secondary pathogens, with predisposing factors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 79 publications
1
7
0
Order By: Relevance
“…The sIgA secreted by epithelial immune cells has an immunoprotective function and is considered the first line of defense in mucosal immunity ( Li et al., 2020 ). Our study showed that E. coli attacked the immune system by decreasing serum immunoglobulins and interfering with the secretion of jejunum sIgA, which is consistent with another E. coli infection study ( Alber et al., 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…The sIgA secreted by epithelial immune cells has an immunoprotective function and is considered the first line of defense in mucosal immunity ( Li et al., 2020 ). Our study showed that E. coli attacked the immune system by decreasing serum immunoglobulins and interfering with the secretion of jejunum sIgA, which is consistent with another E. coli infection study ( Alber et al., 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Generally, the current knowledge about the immune response against APEC is limited as there are only few studies which primarily focused on bacteriological and histopathological examinations of the affected organs such as lung and changes of antibody levels ( 12 ). The immunological basis of protection against APEC as a primary pathogen is described in the current literature which revealed that a pro-inflammatory response and cellular innate immune response play a role in this context ( 13 ). Previous transcriptome studies analysing lung, bone marrow, thymus, bursa, spleen or blood derived leukocytes showed an important function of the innate immune response to APEC ( 14 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous transcriptome studies analysing lung, bone marrow, thymus, bursa, spleen or blood derived leukocytes showed an important function of the innate immune response to APEC ( 14 16 ). As it was reviewed before, in regard to cellular innate immunity, heterophils, macrophages, dendritic cells and thrombocytes are described to be important in the defense against APEC ( 13 ). Innate immune cells recognize distinct pathogen-associated molecular pattern (PAMP) on the bacterial surface, which in turn activates intracellular signaling pathways resulting in antimicrobial activities and the production of pro- and anti-inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in resilience to local E. coli infection between feeding strategies may also be the result of a difference in inflammatory response. The inflammatory response seems to play a larger role in the susceptibility to colibacillosis compared to the adaptive immune response as differences in susceptibility are for instance not related to maternal antibodies ( Ask et al, 2006b ; Ariaans et al, 2008 ; Dwars et al, 2009 ; Peng et al, 2018 ; Alber et al, 2021 ). As indicated in the previous paragraph, early fed broilers may show lower inflammatory responses compared to delayed fed broilers.…”
Section: Discussionmentioning
confidence: 99%